2017
DOI: 10.1002/tox.22494
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis for UVB‐induced phototoxicity in mouse retina

Abstract: Throughout life, the human eye is continuously exposed to sunlight and artificial lighting. Ambient light exposure can lead to visual impairment and transient or permanent blindness. To mimic benign light stress conditions, Mus musculus eyes were exposed to low-energy UVB radiation, ensuring no severe morphological changes in the retinal structure post-exposure. We performed RNA-seq analysis to reveal the early transcriptional changes and key molecular pathways involved before the activation of the canonical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Deficiencies in DNA repair lead to the accumulation of DNA damage and the development of cancer and premature aging. In a previous study, we found that Smug1 was downregulated in ultraviolet B (UVB)-irradiated mouse retinas compared with control retinas [13]. To test the physiological functions of SMUG1, we generated SMUG1 KO cells using the CRISPR/Cas9 genome engineering system.…”
Section: Ablation Of Smug1 Induces Apoptotic Cell Death In Hepatocarcinoma Hepg2 Cellsmentioning
confidence: 99%
“…Deficiencies in DNA repair lead to the accumulation of DNA damage and the development of cancer and premature aging. In a previous study, we found that Smug1 was downregulated in ultraviolet B (UVB)-irradiated mouse retinas compared with control retinas [13]. To test the physiological functions of SMUG1, we generated SMUG1 KO cells using the CRISPR/Cas9 genome engineering system.…”
Section: Ablation Of Smug1 Induces Apoptotic Cell Death In Hepatocarcinoma Hepg2 Cellsmentioning
confidence: 99%
“…In this research, the retina of 10-week-old mice was exposed to 35 mJ/cm 2 UVB once daily for 4 consecutive days. After 2 days of recovery, the mice were sacrificed and the effect of UVB on the retina was studied [169]. Structurally, no changes were seen in the retinal structures after irradiation, and yet, 126 genes were significantly upregulated while 51 other genes were downregulated in the retinal tissue.…”
Section: Uvb Induced Retinal and Potentially Rpe Damage In In Vivo Momentioning
confidence: 99%
“…Structurally, no changes were seen in the retinal structures after irradiation, and yet, 126 genes were significantly upregulated while 51 other genes were downregulated in the retinal tissue. After analysis, these genes can be sorted into 5 categories of genes and the categories were chromatin regulation, stress and signaling, gene expression regulation, RNA processing, and neuronal genes [169]. Based on these categories, it can be seen that UVB does affect gene expression down to the chromosome level and induces cellular stress upon irradiation.…”
Section: Uvb Induced Retinal and Potentially Rpe Damage In In Vivo Momentioning
confidence: 99%
“…The metabolites of tryptophan within the lens absorb UV radiation, decreasing the amount of light transmitted from the lens [18]. By the early 20s, only 0.1% of UV rays can penetrate, and by the age of 60 years, no UV radiation can reach the retina [19], except in the case of aphakia or pseudophakia [20,21].…”
Section: Introductionmentioning
confidence: 99%